Intumescente fire protection of cellular beams - Mesquita, L.M.R. (2015)
Cellular beams are structural steel beams that are deeper than normal rolled sections and have holes cut into their webs. As the web post failure may occur before the section reaches the limiting temperature usually an increase in the fire protection may be required for members with web openings in comparison to its equivalent solid section. The aim of this work is to present an experimental study of unloaded solid and cellular beams with circular holes in fire conditions with and without intumescent fire protection. These preliminary tests are the basis for generating an elemental multi-temperature analysis (EMTA) needed to assess cellular beams with intumescent protection as prescribed by the prEN13381- 9.